ANALYSIS OF FINE STRUCTURE OF CHERT AND BIF BY MEASUREMENT OF HIGH RESOLUTION MAGNETIC FIELD AND SCANNING X-RAY ANALYZED MICROSCOPE - サカイ, ヒデオ; シライ, コタロウ; タカノ, マサオ; ホリイ, マサエ; フナキ, ミノル; SAKAI, Hideo; SHIRAI, Kotaro; TAKANO, Masao; HORII, Masae; FUNAKI, Minoru (National Institute of Polar Research, 1997)
P(論文) The fine structure of chert and BIF was analyzed by magnetic measurement and Scanning X-ray Analyzed Microscope. The magnetic study was done by the HFD system of magnetic field analysis with high Tc (superconducting critical temperature) SQUID. We examined that the HFD system measures the vertical magnetic field around the magnetized sample at high space resolution. The HFD system was applied to Inuyama chert which has a pinkbed layer at the Triassic/Jurassic boundary. The magnetic field at the upper part of the pinkbed layer showed the upward direction and that of the lower chert layer showed the downward direction. Taking the results of rock magnetic study and Scanning X-ray Analyzed Microscope (SXAM) into consideration, the upward magnetic field corresponds to reversed magnetization at the pinkbed layer, which suggests the short reversed polarity in the Nuanetsi normal geomagnetic polarity zone (E. McELHINNY and J. BUREK, Nature, 232,98,1971; D.V. KENT et al., J. Geophys. Res., 100,14965,1995). The HFD measurement of BIF of Antarctica showed the clear striped structure of BIF. The results in this study indicate that HFD measurement with the analysis by SXAM becomes an useful method to investigate the fine structure of geological samples. departmental bulletin paper